Integrating Economic Philosophy into Sierra Leone’s Educational System: A Comparative Strategy for Sustainable Socio-Economic Development - JACKSON, Emerson Abraham (Journal of Research in Educational Sciences; Vol 16 No 2 (2025): JRES, Volume XVI, Issue 2(20), Winter 2025, 2025)
This study advocates for embedding economic philosophy into Sierra Leone’s educational framework, uniting technical economic expertise with critical thinking and ethical reflection to address complex socio-economic challenges. Adopting a conceptual analysis approach, it examines the discipline’s relevance in the national development context and proposes a structured framework for integration, including educator training, curriculum design, and evaluation mechanisms. While recognising barriers such as resource constraints and institutional resistance, it recommends phased implementation with active stakeholder engagement. The anticipated outcome is a generation of economists proficient in theory, skilled in ethical evaluation, and capable of fostering inclusive, resilient, and sustainable development.